Education Financing Management Strategy in the Era of Disruption: Systematic Literature Review and Meta Analysis - Asyiah, Euis; Tarihoran, Naf’an; Nugraha, Enung (Peneliti.net, 2025)
The era of disruption, marked by massive digital transformation, economic uncertainty, and global crises, has posed significant challenges to the management of education financing, demanding more adaptive and sustainable strategies. This research aims to identify and analyze adaptive education financing management strategies in the face of the era of disruption through a systematic literature review and meta-analysis approach. The data collection process was carried out through literature searches from three main databases, namely, ScienceDirect, PubMed, and Mendeley, with a total of 221,131 articles, which went through a gradual filtering process until 5 articles remained selected for in-depth analysis. The meta-analysis results reveal that adaptive financial management capacity has the strongest correlation with the resilience of educational institutions (effect size 0.89, p<0.001), followed by diversification of funding sources (0.66, p<0.01), socio-economic considerations (0.62, p<0.01), and technology integration (0.60, p<0.01). This research identifies four main categories of education financing management strategies: public funding transformation, public-private approach, digital transformation with changes in cost structures, and consideration of socio-economic impacts. The analysis also reveals significant regional variations, with Eastern European approaches emphasizing ranking-based selective financing, Western Europeans focusing on socio-economic impacts, and Latin Americans focusing on the relationship between financial aid and labor market outcomes. The results of this research provide an integrated conceptual framework for a responsive, flexible, and sustainable education financing model in an era of disruption, as well as an empirical basis for education stakeholders in optimizing resource allocation.